1976
DOI: 10.1177/107769907605300205
|View full text |Cite
|
Sign up to set email alerts
|

Public Interest Program Performance of Multimedia-Owned TV Stations

Abstract: Analysis of FCC reports shows group-owned and multimedia-owned stations have at least as much news and public affairs programming as other stations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Cluster 3 (3) Hileman (1953) Radio audience research. Hileman (1953) Referring to policy concerns about the effects of media concentration on content diversity and quality, Wirth and Wollert (1976) analyzed a 1973 FCC TV programming report to compare coverage of news and public affairs across newspaper-owned stations group-owned stations, network affiliates, and VHF (very high frequency) stations. The study is a good example of integrating multiple industry data sources for an integrated analysis.…”
Section: -1969mentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster 3 (3) Hileman (1953) Radio audience research. Hileman (1953) Referring to policy concerns about the effects of media concentration on content diversity and quality, Wirth and Wollert (1976) analyzed a 1973 FCC TV programming report to compare coverage of news and public affairs across newspaper-owned stations group-owned stations, network affiliates, and VHF (very high frequency) stations. The study is a good example of integrating multiple industry data sources for an integrated analysis.…”
Section: -1969mentioning
confidence: 99%
“…Articles analyzing the legal, technical, and regulatory aspects of unlicensed and pirate radio broadcasting (e.g., Jones, 1994;Phipps, 1991) concluded that most pirate radio broadcasting only conveyed rock and progressive dance music, so might run afoul of FCC rules that required radio stations to serve in the broader public interest, convenience, and necessity; they could also be challenged on the basis of illegal and wasteful frequency use (Jones, 1994). Wirth and Wollert (1976) found that most multi-media and group-owned radio stations actually provided more public interest programming than independent stations, countering arguments against cross-ownership and concentration.…”
Section: Table 7 (Continued)mentioning
confidence: 99%